Effect of crude glycerine in supplement on the intake, rumen fermentation, and microbial profile of Nellore steers grazing tropical grass - San Vito, Elias [UNESP]; Messana, Juliana D. [UNESP]; Castagnino, Pablo S. [UNESP]; Granja-Salcedo, Yury T. [UNESP]; Dallantonia, Erick E. [UNESP]; Berchielli, Telma T. [UNESP] (Elsevier, 2016)
The objective of this study was to evaluate the effect of crude glycerine (CG) inclusion in feed supplement (0, 70, 140, 210 and 280 g/kg DM basis of supplement) on the forage intake and digestibility, ruminal fermentation parameters, kinetics of fibre degradation, and rumen microbial profile of Nellore steers grazing on tropical grass. Ten ruminally cannulated Nellore steers [490 kg±47 body weight (BW)] were used in a replicated 5×5 Latin square design with 14-d periods. Steers were individually supplemented at the rate of 300 g/100 kg of BW. Inclusion of CG in the supplement did not affect (P>0.05) dry matter intake, apparent total tract digestibility, ruminal pH (P=0.784) or total ruminal VFA (P=0.291), but linearly decreased the NH3-N concentration (P=0.021). The inclusion of CG in the supplement linearly increased (P <0.001) the molar proportions of butyrate and valerate; linearly decreased the acetate (P=0.007) concentration, thus reducing the acetate to propionate ratio (P<0.001); and did not affect the molar proportions of propionate and isobutyrate. Inclusion of GC had a quadratic effect (P=0.010) on the in situ potential degradable fraction of NDF and rate of fibre degradation (P=0.006). Addition of CG linearly decreased the number of protozoa of the genera Entodinium (P=0.015) and Isotricha (P=0.058) and the relative proportions of Ruminococcus albus (P=0.047) and Ruminococcus flavefaciens in the rumen (P=0.036), but did not affect Fibrobacter succinogenes (P=0.420) or the methanogens (P=0.150). The inclusion of CG in the supplement up to 280 g/kg DM altered ruminal fermentation and negatively affected in situ fibre degradation and the gram-positive cellulolytic bacterial population, but did not affect intake and apparent total tract digestibility for Nellore steers grazing tropical grass.
Keywords: Bacteria; Degradation; Forage; Glycerol; Protozoa